Senegal Cluster Baseline Report - Kumar, Shalander; Yessoufou, Adjani Nourou-Dine; Houessionon, Prosper; Worou, Nadine; Whitbread, Anthony M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This report presents the socio-demographic and economic situation of farmers in the context of farming systems and climate change in the intervention areas of the AICCRA-Senegal project. It also highlights the baseline situation of the key performance indicators of agriculture and livestock value chains, plus the use of climate information and climate-smart agriculture (CSA) innovations. The report has been developed based on the primary data collected from 503 farm households covering both the treatment and control villages in the study region-peanut basin of Senegal. The introductory chapter covers the context of the project, its objectives and methodological aspects. The second part presents characteristics of farms, plus farmers and livestock keepers. The third section describes agricultural systems for the three main agricultural crop value chains, the following section focuses on livestock systems; The fifth and final section is devoted to presentation of the level of knowledge and use of climate information. It also highlights the status of vulnerability/resilience in the face of climate change and variability.